The genetic basis and nutritional benefits of pigmented rice grain - Mbanjo, E.G.N.; Kretzschmar, T.; Jones, H.; Ereful, N.; Blanchard, C.; Boyd, L.A.; Sreenivasulu, N. (Frontiers Media, 2020)
Improving the nutritional quality of rice grains through modulation of bioactive compounds and micronutrients represents an efficient means of addressing nutritional security in societies which depend heavily on rice as a staple food. White rice makes a major contribution to the calorific intake of Asian and African populations, but its nutritional quality is poor compared to that of pigmented (black, purple, red orange, or brown) variants. The compounds responsible for these color variations are the flavonoids anthocyanin and proanthocyanidin, which are known to have nutritional value. The rapid progress made in the technologies underlying genome sequencing, the analysis of gene expression and the acquisition of global ‘omics data, genetics of grain pigmentation has created novel opportunities for applying molecular breeding to improve the nutritional value and productivity of pigmented rice. This review provides an update on the nutritional value and health benefits of pigmented rice grain, taking advantage of both indigenous and modern knowledge, while also describing the current approaches taken to deciphering the genetic basis of pigmentation.